A IMPORTÂNCIA DA LEGISLAÇÃO AMBIENTAL NO CONTROLE DE DERRAMAMENTOS DE ÓLEO NO MAR - Mello, Juliana de Souza (2008)
The preservation of the Environment if became thematic an important one in the world-wide scene, mainly because of it is that the survival of the humanity in the land will be supported. With the natural resources to the disposal of the man, the same only it was to evaluate the harmful consequences of the exploration when it was come across with great followed disasters of the indignation of the society to the being harmed for enterprise activities. In the branch of the petroliferous activities, the profitability thought is not different of the too much industrial activities. However, with a scene of gigantic accidental possibilities, it is necessary to have an operating ambient management and effective in the industrial sector. The study it searches to demonstrate to the positive or negative evolution of the environment questions in the scope of the Brazilian and international legislation and its lacks in the picture of oil spilling in the sea. It is important to analyze the legislation so that effectively it serves of base for, to promote an performance in the prevention and control of oil spilling in the sea. A case study he was inserted to demonstrate the complexity of the relative legislation to the prevention of accidents. The work concludes that the legislation, although complex, is enough to prevent accidents. However, to be more effective, it would be necessary a bigger performance of the control agencies and inspection. One politics of well done and operating environment management can assure that high grade preserved environment.